Utilization of Synthetic Antibody for Fumonisin Determination in Feed and Food - Hasim Munawar; Kal Karim; Sergey A Piletsky (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Fumonisin contamination in food is limited around 2 – 4 ppm and in feed for different animals varies from 5 to 100 ppm. This regulation is to prevent animal and human from carcinogenic effect from fumonisins. Measurement of fumonisins frequently uses chromatography methods such as High-Performance Liquid Chromatography (HPLC) and Liquid chromatography tandem-mass spectrometry (LCMS/MS); however, the sample preparation and analysis process for these methods are costly and time consuming. Immunoassays have also been employed for detecting fumonisins in food or feed. Unfortunately, the instability of antibody to harsh condition such as high temperature and pH becomes the drawback for immunoassay method. Currently, the technology based on molecularly imprinting, which is called synthetic antibody, has been established for replacing antibody functions. Therefore, the aim of this review is to describe development of molecularly imprinted polymer (MIP) in fumonisin analysis in feed and food. Herein, the composition and production of MIP were described comprehensively. Bulk polymerization and solid phase synthesis were methods for production of MIP in micro and nano sizes. The application of MIP was reported for sample preparation as solid phase extraction measured continuously by HPLC showing the high recovery (> 60%). Then, MIP replaced antibody in direct competitive enzyme-linked immunosorbent assay (ELISA) for quantifying fumonisins in maize with high recovery (>90%) and limit detection (2 – 6 pM). Lastly, MIP was also employed in electrochemical sensor application as receptor for recognizing fumonisin in milk and maize. In conclusion, the performance of MIP has been applied successfully for fumonisin analysis comprehensively from sample preparation and quantification. The MIP would be developed for wider application for other toxins in feed or food such as veterinary drug, heavy metals, or pesticides.